Effects of the FCNC Couplings in Production of New Heavy Quarks within Z′ Models at the LHC - V. Çetinkaya; V. Arı; O. Çakır (Advances in High Energy Physics)
We study the flavor changing neutral current couplings of new heavy quarks through the Z′ models at the LHC. We calculate the cross sections for the signal and the corresponding standard model background processes. Considering the present limits on the mass of new heavy quarks and the Z′ boson, we performed an analysis to investigate the parameter space (mixing and mass) through different Z′ models. For FCNC mixing parameter x=0.1 and the Z′ mass MZ′=2000 GeV and new heavy quark mass mt′=700 GeV at the LHC with s=13 TeV, we find the cross section for single production of new heavy quarks associated with top quarks as 5.8 fb, 3.3 fb, 1.5 fb, and 1.2 fb within the Zη′, Zψ′, ZLP′, and Zχ′ models, respectively. It is shown that the sensitivity would benefit from the flavor tagging.